Beyond Financial Outcomes: Evaluating the Multi-Dimensional Impact of Halal Certification on Food and Beverage MSMEs - Andi Rabiul Auliadin; Sitti Aisya; Nur Syamsu; Syaakir Sofyan; Nuriatullah Nuriatullah (Sekolah Tinggi Agama islam Negeri Majene, 2026)
While existing research primarily emphasizes efficiency and market competitiveness, it often overlooks broader dimensions such as customer trust, internal processes, and organizational learning. This study investigates the multi-dimensional impacts of halal certification on MSMEs. Using the Balanced Scorecard framework, this qualitative case study examines the performance of food and beverage MSMEs in Palu City. Data were gathered from 16 purposively selected halal-certified MSMEs through semi-structured interviews and documentation, then analyzed thematically. The findings indicate that the most substantial impact of halal certification extends beyond financial outcomes, emerging most prominently within internal business processes, particularly in areas such as hygiene control, documentation, traceability, raw material selection, and production discipline. These improvements bolster customer trust and product legitimacy, which can facilitate broader market access and more stable sales. However, financial benefits tend to be indirect, depending on an MSME's ability to leverage certification for growth while managing compliance costs. Ultimately, this study highlights that halal certification serves not merely as a regulatory requirement, but as a vital organizational governance mechanism that strengthens business credibility and operational discipline